Efficacy, host-finding ability and application methods of entomopathogenic nematodes to control pupae of Gonipterus sp. 2 (Coleoptera: Curculionidae) - Hurley, Brett P. (University of Pretoria, 2023)
Dissertation (MSc (Entomology))--University of Pretoria, 2023.